Recent Progress in Fused-Ring Based Nonfullerene Acceptors for Polymer Solar Cells - Cui, Chaohua (Frontiers in Chemistry, 2018)
The progress of bulk-heterojunction (BHJ) polymer solar cells (PSCs) is closely related to the innovation of photoactive materials (donor and acceptor materials), interface engineering, and device optimization. Especially, the development of the photoactive materials dominates the research filed in the past decades. Photoactive materials are basically classified as p-type organic semiconductor donor (D) and an n-type organic semiconductor acceptor (A). In the past two decades, fullerene derivatives are the dominant acceptors for high efficiency PSCs. Nevertheless, the limited absorption and challenging structural tunability of fullerenes hinder further improve the efficiency of PSCs. Encouragingly, the recent progresses of fused-ring based A-D-A type nonfullerene acceptors exhibit great potential in enhancing the photovoltaic performance of devices, driving the power conversion efficiency to over 13%. Such kind of nonfullerene acceptors is usually based on indacenodithiophene (IDT) or its extending backbone core and end-caped with strong electron-withdrawing group. Owing to the strong push-pulling effects, the acceptors possess strong absorption in the visible-NIR region and low-lying HOMO (highest occupied molecular orbital) level, which can realize both high open-circuit voltage and short-circuit current density of the devices. Moreover, the photo-electronic and aggregative properties of the acceptors can be flexibly manipulated via structural design. Many strategies have been successfully employed to tune the energy levels, absorption features, and aggregation properties of the fused-ring based acceptors. In this review, we will summarize the recent progress in developing highly efficient fused-ring based nonfullerene acceptors. We will mainly focus our discussion on the correlating factors of molecular structures to their absorption, molecular energy levels, and photovoltaic performance. It is envisioned that an analysis of the relationship between molecular structures and photovoltaic properties would contribute to a better understanding of this kind of acceptors for high-efficiency PSCs.